2014
DOI: 10.1016/j.neubiorev.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

EEG alpha power and creative ideation

Abstract: Highlights► EEG Alpha activity is sensitive to different creativity-related demands. ► Creativity is associated with alpha increases at frontal and right parietal sites. ► Alpha increases during creative cognition reflect internal processing demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
303
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 418 publications
(374 citation statements)
references
References 133 publications
30
303
1
7
Order By: Relevance
“…More recently, researchers have explored the cognitive processes involved in divergent thinking, the ability to generate several novel solutions to open-ended problems. Behavioral (Barr et al, 2014;Silvia, 2012, 2013;Benedek et al, 2014c;Lee and Therriault, 2013;Nusbaum and Silvia, 2011;Nusbaum et al, 2014;Silvia et al, 2013) and neurophysiological (Beaty et al, 2014a,b;Benedek et al, 2014;Fink and Benedek, 2014;Fink et al, 2009;Gonen-Yaacovi et al, 2013) research suggests that higher-order cognitive processes underlie creative cognition, such as controlled memory retrieval, pre-potent response inhibition, fluid intelligence, and working memory capacity. Such processes are hypothesized to support creative thought by providing the executive control needed to manage complex search processes and inhibit salient conceptual information that can interfere with idea generation (Beaty and Silvia, 2012).…”
Section: Domain-general Creative Cognitionmentioning
confidence: 99%
“…More recently, researchers have explored the cognitive processes involved in divergent thinking, the ability to generate several novel solutions to open-ended problems. Behavioral (Barr et al, 2014;Silvia, 2012, 2013;Benedek et al, 2014c;Lee and Therriault, 2013;Nusbaum and Silvia, 2011;Nusbaum et al, 2014;Silvia et al, 2013) and neurophysiological (Beaty et al, 2014a,b;Benedek et al, 2014;Fink and Benedek, 2014;Fink et al, 2009;Gonen-Yaacovi et al, 2013) research suggests that higher-order cognitive processes underlie creative cognition, such as controlled memory retrieval, pre-potent response inhibition, fluid intelligence, and working memory capacity. Such processes are hypothesized to support creative thought by providing the executive control needed to manage complex search processes and inhibit salient conceptual information that can interfere with idea generation (Beaty and Silvia, 2012).…”
Section: Domain-general Creative Cognitionmentioning
confidence: 99%
“…These observations were made in posterior regions, as opposed to our study, in which the increase in this frequency-band was observed over frontal sites. Recent evidence shows that frontal alpha synchronisation is linked to internal and creative thinking (Fink et al, 2009;Fink and Benedek, 2014), which is defined as the generation of original and creative contributions in problem solving and in cognitive processing in general. In their study, Fink et al (2009) elaborated a task where participants had to imagine unusual uses of different objects.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the increasing availability of new neuroscientific methodologies, the topic of creativity has received considerable interest in the neurosciences, with the production of numerous studies investigating the brain activity during different creativity-related tasks and neuroscientific methods (Fink & Benedek 2014). For what concerns methods, because of its low invasiveness and high time resolution, the EEG is the most used technique to investigate mechanisms such as creativity.…”
Section: Methodsmentioning
confidence: 99%